Beyond Nuclear Ambiguity The Iranian Nuclear Crisis and the Joint Comprehensive Plan of Action - Gerli, Michele (Premio Cesare Alfieri «Cum Laude», 2019)
The objective of the thesis was to illustrate the trajectory of Iranian nuclear crisis from the origins of the nuclear program to the Joint Comprehensive Plan of Action (JCPOA), commonly referred as the nuclear deal. The guiding thread was the concept of "nuclear ambiguity", which was addressed in the following terms: the civilian-military application of the atom constituted the primary source and was further exacerbated by several loopholes in the non-proliferation regime; Teheran exploited both sources and developed a large program with possible military dimensions. The JCPOA attempted to break this trend by limiting Iran's program only to peaceful goals and by creating an unprecedented inspection mechanism. In other words, it attempted to go beyond the previous history of ambiguity.